Penerapan Metode Pembelajaran Problem Solving Dalam Meningkatkan Minat Belajar Siswa Di SMP N.1 Hiliserangkai - Nias - Sergius Lay; Kristiana Mendrofa; Patria Fidema Warni Mendrofa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research is motivated by the reality of the learning situation in the classroom where students cannot learn well due to the use of monotonous learning methods from teachers. The purpose of this research is to increase students' interest in learning by using the problem solving learning method. The method used in this research is qualitative with case study research. The results of this study are first, there is an increase in interest in learning caused by the use of problem solving methods. Second, students are increasingly active in the learning process. Third, some teachers have not maximized the use of problem solving methods, which results in less than optimal learning quality. The conclusion of this study is that the problem solving method needs to be implemented by teachers at SMPN 1 Hiliserangkai (Nias Island) so that more students are interested in learning, in addition to other methods that are more varied and interactive.